From seaside to bedside: Current evidence and future perspectives in the treatment of breast cancer using marine compounds - De Sanctis, Rita; Jacobs, Flavia; Benvenuti, Chiara; Gaudio, Mariangela; Franceschini, Raul; Tancredi, Richard; Pedrazzoli, Paolo; Santoro, Armando; Zambelli, Alberto (Frontiers in Pharmacology, 2022)
To date, only few marine natural compounds have been proved to be active in breast cancer (BC). The main marine-derived drugs that have been studied for the treatment of BC are tubulin-binding agents (eribulin and plocabulin), DNA-targeting agents (cytarabine and minor groove binders – trabectedin and lurbinectedin) and Antibody-Drug Conjugates (ADCs). Notably, eribulin is the only approved cytotoxic drug for the treatment of advanced BC (ABC), while cytarabine has a limited indication in case of leptomeningeal diffusion of the disease. Also plocabulin showed limited activity in ABC but further research is needed to define its ultimate potential role. The available clinical data for both trabectedin and lurbinectedin are of particular interest in the treatment of BRCA-mutated tumours and HR deficient disease, probably due to a possible immune-mediated mechanism of action. One of the most innovative therapeutic options for the treatment of BC, particularly in TNBC and HER2-positive BC, are ADCs. Some of the ADCs were developed using a specific marine-derived cytotoxic molecule as payload called auristatin. Among these, clinical data are available on ladiratuzumab vedotin and glembatumumab vedotin in TNBC, and on disitamab vedotin and ALT-P7 in HER2-positive patients. A deeper knowledge of the mechanism of action and of the potential predictive factors for response to marine-derived drugs is important for their rational and effective use, alone or in combination. In this narrative review, we discuss the role of marine-derived drugs for the treatment of BC, although most of them are not approved, and the opportunities that could arise from the potential treasure trove of the sea for novel BC therapeutics.